Feasibility of using AI-assisted monitoring to improve school meal programs: A pilot study in southern Malawi - Ndolo, Victoria; Chimwala, Dalitso; Musa, Frank; Bempong, Silas; Bannerman, Boateng; Nwabuikwu, Odiche; McCloskey, Pete; Folson, Gloria; Gelli, Aulo (International Food Policy Research Institute, 2024)
Reaching over 400 million children for investments of $50 billion a year, school meals are popular safety nets with documented impacts across social protection, education and nutrition dimensions1. Governments have linked school meals to food system transformation, where public procurement is used as an outlet for farmers, through Home-Grown School Meal Program (HGSMP) approaches. HGSMPs have the potential to improve children’s diets, whilst also providing a market for farmers. Implementing school meals that meet quality standards, including food, nutrition, smallholder sourcing and environmental requirements is critical. In practice, data on the quality of school meal delivery is scarce. There is also an opportunity to improve HGSMP menus, optimizing on foods that are nutritious, locally available and “climate-smart”.